Env-pseudoviruses based on the HIV-1 genetic variant circulating in Siberia - N. B. Rudometova; A. A. Fando; D. N. Shcherbakov; B. N. Zaitsev; A. P. Rudometov; L. I. Karpenko (Вавиловский журнал генетики и селекции, 2025)
Despite numerous efforts of the global community, it is still not possible to stop the HIV/AIDS pandemic. To stop the spread of the virus, an effective preventive vaccine is needed, as well as the search for new antiviral agents. In order to be able to quickly and adequately evaluate the developed vaccine constructs, characterize HIV-specific antibodies and potential drugs, a reliable testing method is needed. In this regard, pseudotype neutralization assays using a panel of Env-pseudoviruses of different HIV-1 subtypes has proven itself well. Currently, separate panels of Env-pseudoviruses of the main genetic subtypes of HIV-1 (A, B, C and a number CRFs) have been created. These panels are necessary to obtain standardized data sets that can be used to rank the effectiveness of the vaccine and identify promising candidates for further study. Currently, the HIV-1 subtype A6 dominates in the European part of Russia, and the recombinant form CRF63_02A6, which has currently been detected in more than 80 % of new HIV-1 cases in Siberia, dominates in Siberia. The aim of this work was to expand and characterize the collection of Env-pseudoviruses obtained on the basis of the recombinant form CRF63_02A6 of HIV-1 circulating in Siberia. In this study, two new variants of Env-pseudoviruses based on CRF63_02A6 of HIV-1 were obtained, characterized, and included in our collection. At present, the collection includes 13 Env-pseudoviruses that are CCR5-tropic. Phylogenetic analysis of the full-length nucleotide sequences of the env gene confirmed that all 13 pseudoviruses cluster with the reference sequences of the recombinant form CRF63_02A6. The Env-pseudoviruses were characterized using broadly neutralizing antibodies (bnAbs) targeting different regions of vulnerability of HIV-1 located on the surface of Env glycoprotein complexes. It was shown that the Env-pseudoviruses are sensitive to neutralization by bnAbs VRC01 and 10E8; moderately sensitive to neutralization by bnAbs PG9 and PGT126; and resistant to neutralization by antibodies 2G12 and 2F5. The resulting collection is an important addition to the existing panels of pseudoviruses against other HIV-1 subtypes in the world.